Cognitive decline associated with anticholinergics,benzodiazepines and Z-drugs: Findings from The Irish Longitudinal Study on Ageing (TILDA) - Moriarty, Frank; Kenny, Rose (My University, 2020)
Aims: To estimate the association between patterns of anticholinergic, benzodiazepine and Z-drug medication use and change in cognitive function in middle-aged and older adults. Methods: This prospective cohort study used data from the first three waves of The Irish Longitudinal Study on Ageing (TILDA), including community-dwelling adults aged ≥50 years followed for up to 4 years (n = 7027). Cognitive function was assessed using the Mini Mental State Examination, animal naming test and word recall tests. Regular medication use was self-reported at baseline and follow-up interviews at 2 and 4 years. Pharmacy dispensing claims for a subset (n = 2905) allowed assessment of medication use between interviews and cumulative dosage. Medication use at consecutive waves of TILDA was analysed in relation to change in cognitive function between waves. Results: Strongly anticholinergic medications (Anticholinergic Cognitive Burden scale 3), benzodiazepines and Z-drugs were reported by 7.3%, 5.8% and 5.1% of participants, respectively, at any time during the study. Adjusting for potential confounders, new anticholinergic use between interviews was associated with change in recall score (−1.09, 95% confidence interval −1.64, −0.53) over 2 years compared to non-use, but not with MMSE (0.07; 95% CI −0.21, 0.34) or animal naming (−0.70; 95% CI −1.43, 0.03). The pharmacy claims analysis was consistent with this finding. Other hypothesised associations were not supported. Conclusions: Except for new use of anticholinergic medications, no other findings supported a risk of cognitive decline over 2-year periods in this middle-aged and older cohort. Patients and prescribers should weigh this potential risk against potential benefits of commencing anticholinergic medications.
PUBLISHED
doi:10.1111/bcp.14687
Keywords: anticholinergic medication, benzodiazepines, cognitive function, pharmacoepidemiology, Z-drugs; Ageing